Application of semitransparent photovoltaics in transportation infrastructure for energy savings and solar electricity production: Toward novel net‐zero energy tunnel design. (19th August 2019) - Sun, David; Athienitis, Andreas; D'Avignon, Katherine
Abstract: Lighting subsystems account for up to 50% of the energy consumption of a typical tunnel. Day‐time lighting levels account for over two‐thirds of the total system lighting power; their periodic nature creates daily peaks in the tunnel's energy load profile. This paper studies the integration of semitransparent photovoltaic (STPV) cells into sunscreen structures installed above tunnel entrances to reduce tunnel lighting requirements and offset their day‐time lighting loads using energy generated from PVs. The electrical lighting load of a typical 1‐km length road tunnel with and without STPV sunscreen structures was modeled to establish the potential for energy savings. Using a daylighting and energy modeling plug‐in called DIVA, the transparencies and ratios of photovoltaics (PV) to glass of a STPV sunscreen that are in accordance with the luminance reduction code requirements were determined. Reduced lighting requirements over the whole tunnel length, including the threshold, transition, and interior lighting zones of the tunnel were considered, resulting in significant energy savings. The annual power production of the sections covered with STPV was then simulated using the PVsyst software. The integration of PV cells resulted in an annual energy production that reduced annual net‐energy use by up to 7% and with the potential to reduce electric lighting loads by up to 60% during the day‐time. Results also demonstrated that STPV sunscreens have the potential to meet luminance requirements if supplemented with an intelligent lighting control system. Abstract : Lighting systems in tunnels can consume 50% of the energy needs of a typical tunnel, and intense day‐time lighting loads create peaks in tunnel load profiles. This paper studies the application of matrix‐based and intrinsic semitransparent photovoltaic (SPTV) materials into sunscreen structures installed above tunnel entrances. It demonstrates that SPTV sunscreens can curtail energy use and peak loads by reducing glare from the sun, reducing lightning requirements, offsetting artificial lighting loads with sunlight, and producing energy concurrent with peak loads.